2004
DOI: 10.1016/j.biomaterials.2003.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Porous poly(α-hydroxyacid)/Bioglass® composite scaffolds for bone tissue engineering. I: preparation and in vitro characterisation

Abstract: Highly porous composites scaffolds of poly-D,L-lactide (PDLLA) and poly(lactide-co-glycolide) (PLGA) containing different amounts (10, 25 and 50wt%) of bioactive glass (45S5 bioglass ® ) were prepared by thermally induced solid-liquid phase separation (TIPS) and subsequent solvent sublimation. The addition of increasing amounts of bioglass ® into the polymer foams decreased the pore volume. Conversely, the mechanical properties of the polymer materials were improved. The composites were incubated in phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
220
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 319 publications
(243 citation statements)
references
References 33 publications
18
220
0
5
Order By: Relevance
“…The addition of 15 vol.% Bioglass® tended to reduce the porosity by ~1% when compared to that of 100% PDLLA and of 2 vol.% PDLLA/Bioglass® foams. This is consistent with previous work where the porosity was also shown to decrease with increasing filler content (up to 40 wt.% Bioglass®) [12]. However, it has been reported that at high filler loadings the pore shapes become increasingly rugose, thereby resulting in a moderately less well-ordered structure [2,12].…”
Section: Characterisation Of Foam Pore Structuresupporting
confidence: 92%
See 3 more Smart Citations
“…The addition of 15 vol.% Bioglass® tended to reduce the porosity by ~1% when compared to that of 100% PDLLA and of 2 vol.% PDLLA/Bioglass® foams. This is consistent with previous work where the porosity was also shown to decrease with increasing filler content (up to 40 wt.% Bioglass®) [12]. However, it has been reported that at high filler loadings the pore shapes become increasingly rugose, thereby resulting in a moderately less well-ordered structure [2,12].…”
Section: Characterisation Of Foam Pore Structuresupporting
confidence: 92%
“…PDLLA and PDLLA/Bioglass®-filled composite foams were prepared by TIPS and subsequent solvent sublimation, which has been described in detail elsewhere [12,13]. Monolithic foams were produced with dimensions of 90 mm diameter and varying in thickness 7-10 mm due to the shape of the vessel base used in fabrication.…”
Section: Foam Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Working with polymerbased composites offers a wider range of mechanical properties closer to bone, osteocondution induced by ceramics and a better control of resorption rate. [25][26][27] Polymer-based foams can be processed in different ways: solvent casting/particulate leaching, 28,29 thermally induced phase separation, or emulsion freezedrying, 30-33 gas foaming. [34][35][36] The latter technique has the main advantage of avoiding the use of potentially toxic organic solvents.…”
Section: Introductionmentioning
confidence: 99%